An investigation into irreducible autocatalytic sets and power law distributed catalysis - Hordijk, W; Hasenclever, L; Gao, J; Mincheva, D; Hein, J (Kluwer Academic Publishers, 2014)
RAF theory has been established as a useful and formal framework for studying the emergence and evolution of autocatalytic sets. Here, we present several new and additional results on RAF sets. In particular, we investigate in more detail the existence, expected sizes, and composition of the smallest possible, or irreducible, RAF sets. Furthermore, we study a more realistic variant of the well-known binary polymer model in which the catalysis events are assigned according to a power law distribution. Together, these results provide further insights into the existence and structure of autocatalytic sets in simple models of chemical reaction systems, with possible implications for theories on the origin of life. © 2014 Springer Science+Business Media.